The Relationship Of The Duration Of Type 2 Diabetes Mellitus With Peripheral Neuropathy - T. Eltrikanawati Eltrikanawati (Institute of Computer Science (IOCS), 2021)
Patients with diabetes mellitus ≥ 5 years of age can cause diabetic peripheral neuropathy, which is a symmetrical peripheral nerve disorder characterized by sensory, motor and autonomic disorders that affect the outer leg nerves. The purpose of this study was to determine the correlation between duration of suffering from diabetes mellitus and the occurrence of peripheral neuropathy. This type of research is analytic with a cross sectional design, a sample of 52 respondents who are in the working area of ​​Puskesmas Tiban Baru Batam City, using purposive sampling with MNSI (Michigan Neuropathy Screening Instrument) questionnaire. The results of this study found that most people with diabetes mellitus ≥ 5 years were 31 respondents (59.6%), most of them had peripheral neuropathy as many as 31 respondents (59.6%) and almost all patients with diabetes mellitus ≥ 5 years had peripheral neuropathy as many as 24 respondents (77.4%). From the results of the chi suare statistical test p value = 0.001 (0.05), Ha is accepted, this indicates that there is a significant relationship between the duration of suffering from diabetes mellitus and the occurrence of peripheral neuropathy. People with diabetes mellitus are obliged to maintain a pattern of daily life such as physical activity, diet, and regularity in taking medication to reduce the risk of peripheral neuropathy.